Improving bilingual higher education: Training university professors in content and language integrated learning - Birgit Strotmann; Victoria Bamond; José M. López Lago; María Bailen; Sonia Bonilla; Francisco Montesinos (Laureate Education Inc, 2014)
Few studies have been conducted at the tertiary level on Content and Language Integrated Learning (CLIL). The current study aims to gather and share preliminary data concerning CLIL in higher education at several universities in different countries. A questionnaire and brief description of the project and its objectives were emailed to all teachers at a Spanish university listed as having taught content courses in English in the last academic year, and to all the Language Center directors within the network with instructions to pass the questionnaire along to the CLIL teachers at their respective universities. The questionnaire was answered by 168 teachers, with 79% of responses (n=133) coming from four universities in Spain, Malaysia, P.R. China, and Turkey. The questionnaire results were exported to Excel and analyzed using statistical software. This preliminary phase of the research project, in which quantitative data has been analyzed, shows that CLIL teachers are intrinsically-motivated, language proficient, and aware of the need to adapt material to the bilingual classroom. In the next, qualitative phase of the project, issues regarding English language assessment, use of L1 in the classroom and scaffolding will need to be analyzed in depth in order to propose guidelines for future good practices and bilingual teacher training. DOI: 10.18870/hlrc.v4i1.198